PENGARUH TERAPI MADU TERHADAP PENURUNAN FREKUENSI BUANG AIR BESAR PADA ANAK USIA 0-2 TAHUN YANG MENGALAMI DIARE DI RUMAH SAKIT UMUM DAERAH DELI SERDANG LUBUK PAKAM TAHUN 2020 - Juni Mariati Simarmata; Pitri Ani; Dwi Astuti; Syatriawati Suhaimi; Beti Susanti Tarigan; Samuel Ginting; Rosita Ginting; Wilda Wahyuni Siregar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2021)
Diarrhea is a disease characterized by changes in the shape and consistency of stools were soft until melted and increased frequency of bowel movements than usual, which is 3 times or more a day which may be accompanied by vomiting or bloody stools. Diarrheal disease is still a global problem with the degree of morbidity and mortality are high in many countries, especially in developing countries and as one of the major causes of morbidity and mortality of children in the world. From laboratory studies and clinical trials, pure honey has bactericidal activity against several organisms that can entropathogenic, including species of Salmonella, Shigella, and E. coli. The goal of this research was to determine the effect of honey therapy to decrease the frequency of bowel movements in children aged 0-2 years who had diarrhea in district general hospitals deli serdang Lubuk pakam 2020. This research was conducted by quasi experimental research design through the design time series design , The sample in this study using the technique of sampling purvosive the number of 10 people as respondent data obtained using observation sheets and tested by t-test (paired sample t-test) and computer assistance. From the results of research conducted on 10 respondents obtained results p <Î± (0.005 <0.05), which describes the influence of honey therapy to decrease the frequency of bowel movements in children aged 0-2 years who had diarrhea in hospital common areas serdang deli depths Pakam. Thus Ho is rejected and Ha accepted.